Accounting and management systems as the basis of enterprise development - E. V. Gavrichenko; A. A. Ilina (Вестник университета, 2023)
The article presents a study on the management of accounting systems, its current state, as well as on the difficulties that arise in the work of enterprises under the risks’ influence. The impact of the Covid-19 pandemic has been studied on the economic activity of the enterprise and on the reporting formation. The main changes in the organization of the company’s activities in modern conditions and costs affecting the accounting statements have been reflected. The accounting problems in conditions of uncertainty and violation of information exchange between responsibility centers have been identified. The existing systems’ comparative analysis of accounting, management accounting and risk management has been compiled. The benefits of optimizing accounting systems under the influence of modern risks have been formulated and information on them has been detailed, in accordance with the specifics of conducting financial and business operations at enterprises. The interrelation of accounting and risk management systems has been established, aimed at minimizing losses in the implementation of the enterprise’s activities in conditions of uncertainty.